Communication Between TSX Micro 37-21 PLCs on Beverage Production Plant - Wicaksono, Handy; Udayana, Chandra; Ferdinando, Hany (Jurnal Teknik Elektro, 2006)
Programmable Logic Controller (PLC) is the most famous controller in industry. Because the process in industry is getting more and more complex than before, the usage of more than one PLC is needed and the communication between them have to be existed. This paper describes about the study of communicating two Schneider TSX Micro 37-21 PLCs in order to control the miniature of beverage production. The usual (and expensive) way to communicate them is using converter module TSX P ACC 01. Less expensive way uses original converter cable TSX PCX 1031 that connect to the ports of PLCs (TER and AUX port) which will be explained here. PL7 Pro V 4.0 software is used to program the PLCs. The communication cannot be established due to some improper addressing. The exploration is continued to the serial communication. It is found that the system uses RS 485. Abstract in Bahasa Indonesia : Programmable logic Controller (PLC) adalah kontroler yang paling populer di dunia industri. Karena proses di industri semakin kompleks, diperlukan penggunaan lebih dari satu PLC yang dapat berkomunikasi satu sama lain. Penelitian ini menjelaskan tentang studi dalam mengkomunikasikan 2 PLC TSX Micro 37-21 dari Schneider untuk mengendalikna miniatur produksi minuman. Cara yang umum (dan mahal) ialah dengan menggunakan modul TSX P ACC 01. Cara yang lebih murah ialah menggunakan kabel converter asli TSX PCX 1031 yang menghubungkan port LPC (TER dan AUX port) yang akan dijelaskan di sini. Software PL7 Pro V 4.0 digunakan untuk memprogram PLC. Komunikasi tidak dapat dilakukan karena pengalamatan yang kurang tepat. Eksplorasi dilanjutkan kepada komunikasi serialnya. Dari percobaan ditemukan bahwa sistem ini menggunakan RS 485. Kata kunci: PLC TSX Micro 37-21 Schneider, komunikasi antar PLC, miniatur plant produksi minuman.